Аналіз індикаторів впливу на економічну безпеку підприємств в контексті соціогуманітарної компоненти - Vivchar, Oksana; Redkva, Oksana (Dr. Viktor Koval, 2018)
Introduction. The level of economic security of enterprises is characterized by many indicators. The assessment of the state of economic security of enterprises is carried out through a system of criteria and indicators. The criterion of enterprises economic security is a measure of the state of the entity in terms of compliance with the established indicators of its activity with pre-established indicators reflecting the essence of economic security. Therefore, the problem of analyzing indicators of enterprises economic security and developing measures to improve their economic component in the context of the socio-humanitarian component. Aim and tasks. Justification of the need to develop measures to improve the assessment of economic security of enterprises based on the impact of indicators in the context of the socio-humanitarian component. On the basis of this goal, the question arises of solving such problems as: the possibility of developing a unified conceptual approach and tools for assessing the impact of indicators on the organization's economic security; developing measures to improve the economic component of enterprises in the context of the socio-humanitarian component. Results. For the analysis of the economic security state, indicators were chosen that characterize economic security in different spheres of enterprise activity according to the recommendations. For each indicator a matrix of values with the enterprises and indicators of values by years was formed. The analysis uses a multidimensional logit model, a case of binary selection. The model does not take into account group effects, that is, there is no analysis of fixed effects. In order to avoid cross-effects, when not only the variable itself influences the likelihood of a crisis, but the public crisis begins to affect the behavior of the variable, two groups of models are built: for the first group of regressions from the sample, all observations after the first year of crises are excluded; for the second group of regressions all data were used except for the crisis years after the first year of the crisis. Conclusions. Based on the analysis of the investigated indicators and the determination of t the parameters of enterprises economic security in addition to economic methods, administrative and socio-psychological means can be used. They include methods of influencing individual workers, groups of employees or the collective as a whole to form a corporate culture that will help achieve the goals of this enterprise, will reduce the impact of socio-humanitarian factors of economic security on the enterprise. These methods include: training staff rules of safe behavior; work with managers, whose behavior serves as a reference for the company's staff; development of a program of work with new employees and its implementation; formation and adjustment of traditions of the enterprise; regulation of interpersonal and intergroup relations; moral encouragement; social planning; other methods. Quick methods for certain enterprises were also proposed to improve the economic component of their operation.